Efficiency of monitor roof in maintaining the thermal conditions of indoor air and water in a medium scale enclosed tropical prawn hatchery building - Kamarudin, Mohd Salleh; Kamarudin, Ahmad Kamil; Sheikh Ahmad, Sabarinah; Salleh, Elias (Asian Fisheries Society, 2015)
This paper investigated the effects of roof design on the thermal conditions of indoor air and larviculture tank water of a tropical freshwater prawn Macrobrachium rosenbergii (de Man 1879) hatchery building. The research method was through a simulation study, using Integrated Environmental Solutions Virtual Environment (IES VE) software and the building modelled was based on an existing medium scale enclosed freshwater prawn hatchery. Monitor roof (vented ridge) was compared with the existing pitched roof design. The results showed the vented monitor roof design provided a considerable improvement to the indoor thermal environment of the prawn hatchery. The indoor air temperatures recorded under the monitor roof was close to the upper human acceptable thermal limit (34.0 °C) and some of the thermal readings were adequate for humanly comfortable condition. The indoor air temperatures became totally acceptable for the occupants during daytime through the installation of reflective aluminium foil (RAF) to the monitor roof. Therefore, the combination of monitor roof and RAF was recommended to achieve acceptable indoor air thermal condition for occupants while successfully maintaining the water thermal requirement for optimal prawn larval growth.